ANALISIS STATUS KEBERLANJUTAN PENGELOLAAN AIR BAKU DI KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Ridwan Adi Surya; M. Yanuar J. Purwanto; Asep Sapei; Widiatmaka Widiatmaka (Environmental Research Center (PPLH) of Udayana University, 2014)
The water supply to support the development and human needs need to be guaranteed forthe sustainable condition. Decreased water availability and increased water demand hasoccurred in Konawe Regency Southeast Sulawesi Province. In order to the management forwater supply in Konawe Regency can take place in a sustainable condition, it is necessary toapply the concept of sustainable development through the conservation of water resources.This study aims to analyze the sustainability of the status of water management for sustainablewater supply in Konawe Regency, and analyze the important factors that affect the sustainabilityof water management in the Konawe Regency. The analytical method used is a MultiDimensional Scaling called Rap-Konawe. The results are expressed in terms of index andstatus of sustainability. The analysis on the five dimensions indicate that the ecologicaldimension is sustainable enough (52.36%), economic dimension is less sustainable (36.93%),social dimension is less sustainable (34.16%), technology dimension is less sustainable(35.39%), and institutional dimension is less sustainable (35.39%). There was 12 attributesneed to be taken care immediately because of the sensitive affect on the increase of index andsustainability status.